Immunogobulins and Thermal Burns Infections - N. K. Mehdiratta; H. P. Singh (Indian Journal of Plastic Surgery)
Burns patients have higher susceptibility to infections, causes of which are many fold. Leakage of immunoglobulins in blister fluid is one of them. The present work was undertaken to find out the relationship between the types of infections and the levels of various immunoglobulins in the sera of burn patients. Radial immunodiffusion technique of Mancini was utilized to measure the levels. It was observed that all types of infections produced rise in immunoglobulin levels. In mixed and Pseudomonas infections the rise of all major immunoglobulins was found statistically insignificant while in fungally invaded patients IgM levels were significantly raised but on excision of the invaded areas, IgM levels dropped to within normal range.